The periodic kingdom : a journey into the land of the chemical elements - Atkins, P. W. (Peter William), 1940- (New York : BasicBooks, 1995)
Uses the periodic table of chemical elements to present principles in chemistry and a review of discoveries in chemistry that have influenced the world.
Includes bibliographical references (p. [151]-152) and index.
Library Journal Starred.
Wilson's Public Library.
Wilson's Senior High School.
Adult
Keywords: Chemical elements; Periodic law; Chemical elements; Chemistry; Periodic law